Capacitive driven-right-leg circuit design - Haberman, Marcelo Alejandro (2015)
Capacitive electrodes allow to pick-up biopotentials through a dielectric layer, without using electrolytes. However, this technique is vulnerable to electric-field interference, mainly to common mode voltages produced by the 50 Hz power-line. A fully Capacitive Driven Right Leg (CDRL) circuit is proposed to reduce the patient common mode voltage vCM. The design of this circuit takes into account several factors as electrode impedance, stray coupling capacitances and amplifier transfer function response. All these parameters are addressed to ensure the circuit's stability in most biopotential acquisition scenarios. Monte Carlo analyses were performed to find the worst conditions, resulting in a maximum CDRL gain between 70 and 80 dB. The CDRL was implemented as an independent block that can be used for different applications such as ECG, EMG or EEG. Several experimental results are presented, showing good quality recordings even using SE amplifiers, an appropriate approach for multichannel acquisition systems.